SOCIOLOGICAL PERSPECTIVE OF EDUCATION IN VIEWING VIOLENCE IN THE WORLD OF EDUCATION IN INDONESIA - Hikmat (GoAcademica Research dan Publishing, 2021)
The emergence of subject-object relations in education causes delinquency among teenagers. This delinquency then causes the emergence of violence that occurs in education. As a sociological study of education, this one examines how the phenomena of violence is viewed from a sociological standpoint. This study will use a qualitative approach by using data from various research results and previous studies that are still relevant to this research. The study results found that student delinquency cannot be separated from the influence of the subject-object relationship pattern built-in science. This relationship pattern stems from the lack of objectivity of the Indonesian education system, including its principles, aims, social organization, curriculum, teaching techniques, evaluation, students, educators, facilities, and funding.